Climatic Features and Their Relationship with Tropical Cyclones Over the Intra-Americas Seas - Amador Astúa, Jorge Alberto; Alfaro Martínez, Eric J.; Rivera Fernández, Erick; Calderón Solera, Blanca (2010)
In this chapter, indexes of the Intra-Americas or Caribbean Low-Level Jet (IALLJ or CLLJ, respectively), Niño 3, Tropical North Atlantic (NATL), Atlantic Multidecadal Oscillation (AMO), and Outgoing Long Wave Radiation (OLR) are quantified for the period 1950–2007, to study their relationship with tropical cyclone (TC) frequency for summer–autumn of the Northern Hemisphere. A remarkable inverse relationship is found between both, the strength of the wind speed at 925 hPa and the vertical wind shear at low levels, and the monthly relative frequency of TCs for two selected areas in the Caribbean. The July peak in wind speed and low-level vertical wind shear are associated with a minimum in the monthly relative frequency of TCs. On the contrary, a decrease in the wind speed and vertical shears are associated with a maximum value of the relative frequency of TCs. Stronger (weaker) than normal IALLJ summer winds (July–August) during warm (cold) ENSO events imply a stronger (weaker) than normal vertical wind shear at low-levels in the Caribbean. This condition may inhibit (allow) deep convection, disfavoring (favoring) TC development during these months. Correlation values of the monthly mean CLLJ core winds and the monthly normalized values of NATL – Niño 3 index for 1950–2007 showed statistical significance greater than 99% during July–August. During El Niño years, low-level wind increases at the jet core strengthening the low level convergence near Central America at the jet exit and the low-level divergence in the central Caribbean at the jet entrance. The descending motion associated with the latter acts as an inhibiting factor for convection and TC development. TC activity in the Caribbean is not only sensitive to ENSO influences, but to the strength of the CLLJ vertical wind shear, to barotropic energy conversions induced by the lateral wind shear, to the intensity of the regional scale descending motion associated with the jet entrance, and to the SST cooling generated by the CLLJ at the sea surface. ...